Androgen Receptor Immunohistochemical Expression in Undifferentiated/Dedifferentiated Endometrial Carcinoma. (January 2022) - Cao, Jin; Hacking, Sean; Chavarria-Bernal, Hector D.; Bhuiya, Tawfiqul A.; Khutti, Seema
Abstract : Uterine undifferentiated (UC)/dedifferentiated (DEAC) carcinomas are rare malignant neoplasms. They tend to pursue an aggressive clinical course with an advanced stage at presentation. It has been found that androgen receptor (AR) might play a role as a prognostic and therapeutic marker in endometrial carcinoma. However, its expression in UC/DEAC has not been investigated. Herein, the aim of this study was to evaluate the expression of AR along with estrogen receptor (ER), progestin receptor (PR), and HER2 in UC/DEAC and also in other subtypes of high-grade endometrial carcinomas. Review of our pathology database over the period of 2011 to 2019 identified 16 UC/DEAC cases (N=16). We also randomly selected other high-grade endometrial carcinomas including FIGO 3 endometrioid carcinoma (N=9), serous carcinoma (N=8), clear cell carcinoma (N=12) and carcinosarcoma (N=10) for comparison. Immunohistochemical stains for AR, ER, PR, and HER2 were performed on all 55 cases. The protein expression was evaluated both quantitatively and qualitatively. In DEAC cases both the undifferentiated component and the well-differentiated component were recorded separately. Overall, variable degrees of AR reactivity (by Allred scoring method) was present in 63% of UC/DEACs(10/16), 67% of FIGO 3 endometrioid carcinomas (6/9), 88% of serous carcinomas (7/8), 80% of carcinosarcomas (8/10), and 9% of clear cell carcinoma (1/12). AR expression was most often seen with PR (70%) or ER (60%) staining in UC/DEACs. Thirteen cases of UC/DEACs were positive for at least 1 hormone receptor. HER2 was negative in all UC/DEACs. Almost all other high-grade carcinoma cases were negative for HER2 except 20% of carcinosarcoma (2/10) and 13% of serous carcinoma (1/8) which showed 3+ HER2. Loss of AR appears to be associated with worse clinicopathologic parameters in UC/DEAC. AR is highly expressed in UC/DEAC, and in the majority of FIGO 3 endometrioid carcinomas, serous carcinomas, and carcinosarcoma. These findings suggest a potential role for androgen inhibitors in the management of patients with these tumors.